Promising methods for detection of novel coronavirus SARS‐CoV‐2. Issue 1 (23rd March 2020) - Liu, Ran; Fu, Aisi; Deng, Zixin; Li, Yan; Liu, Tiangang
Abstract: A very recent outbreak of the novel coronavirus, COVID‐19, in the city of Wuhan, China, in December 2019 and its subsequent spread within and across China have resulted in several deaths and infections. Presently, nucleic acid amplification test is essential for the confirmation of COVID infection. In this report, we summarized the six promising methods, including whole‐genome sequencing, real‐time reverse transcription polymerase chain reaction, nanopore target sequencing, antibody‐based immunoassay techniques, use of paper‐based biomolecular sensors, and the clustered regularly interspaced short palindromic repeats‐Cas system‐based technology, which can also be deployed for the detection of SARS‐CoV‐2. We further introduced the principles of these methods, discussed the scope and practicability of application of the available products and methods, and highlighted the potential approaches to develop additional products and techniques for early diagnosis of COVID‐19. Abstract : The development of antibody‐based immunoassay or nucleic acid testing for detection of SARS‐CoV‐2 infection has become critical for COVID‐19 outbreak control. We introduced the principles of these methods, discussed the scope and practicability of application of the available products and methods, and highlighted the potential approaches to develop additional products and techniques for early diagnosis of COVID‐19.